2016
DOI: 10.1155/2016/2401496
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Sensitive Radial Basis Function Neural Network Classifier for Software Defect Prediction

Abstract: Effective prediction of software modules, those that are prone to defects, will enable software developers to achieve efficient allocation of resources and to concentrate on quality assurance activities. The process of software development life cycle basically includes design, analysis, implementation, testing, and release phases. Generally, software testing is a critical task in the software development process wherein it is to save time and budget by detecting defects at the earliest and deliver a product wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…Results showed that the proposed technique outperformed other modern methods. The researchers in [25] proposed a conventional radial basis function-based technique integrated with a novel adaptive dimensional biogeography-based optimization model for software-defect predication. Five NASA datasets from the PROMISE repository were used for experimental analysis, the results of which showed that the proposed technique is effective compared to earlier proposed models.…”
Section: Related Workmentioning
confidence: 99%
“…Results showed that the proposed technique outperformed other modern methods. The researchers in [25] proposed a conventional radial basis function-based technique integrated with a novel adaptive dimensional biogeography-based optimization model for software-defect predication. Five NASA datasets from the PROMISE repository were used for experimental analysis, the results of which showed that the proposed technique is effective compared to earlier proposed models.…”
Section: Related Workmentioning
confidence: 99%
“…Results reflected that Decision Tree achieved 0.8 and 0.9 AUC scores for AR1 and AR6 respectively which were better than other used techniques. Researchers in [6] presented a software defect prediction technique using Conventional Radial Basis Function along with novel Adaptive Dimensional Biogeography-based optimization model. For experiment, five NASA datasets from PROMISE repository were used and the results showed the higher accuracy of proposed technique as compared to early used techniques.…”
Section: Related Workmentioning
confidence: 99%
“…Software defect prediction has attracted the attention of scholars in knowledge discovery and data mining fields. Many scholars have considered numerous machine learning algorithms to tackle the classification problems related to software defect prediction [9][10][11][12][13][14][15][16][17][18].…”
Section: Related Workmentioning
confidence: 99%
“…Researchers in a study by [14], detected faulty components by applying the radial basis function neural network with novel adaptive dimensional biogeography-based optimization model to investigate five NASA datasets from the PROMISE repository. Results were satisfactory compared to conventional models.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation